2011
DOI: 10.5137/1019-5149.jtn.4965-11.1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diesel exhaust particles on neural tube development in the early stage chicken embryo

Abstract: AIm: Particulate matter is an important air-pollutant and its toxicity has been reported. Diesel exhaust particles (DEP) constitute a large portion of particulate matter. Therefore, we established our study to investigate the effects of DEP on neural tissue in early stage chicken embryos. mAterIAl and methOds: Four study groups and one control group, each of which included 24 objects were designed. Eggs were incubated for 30 hours. Solutions of DEP containing 10, 50, 100, and 200 µg/0.1 ml were prepared with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Many studies have been done on chicken embryos to investigate the etiology of NTD. They evaluated the effects of environmental factors and drugs (Cetinkal et al, 2010;Dalgic et al, 2009;Guvenc et al, 2013;Simsek et al, 2012;Temiz et al, 2009;Whitsel et al, 2002). In this study, it was observed that the width of the neural tube was altered with the Riparin III concentrations evaluated.…”
Section: Discussionmentioning
confidence: 70%
“…Many studies have been done on chicken embryos to investigate the etiology of NTD. They evaluated the effects of environmental factors and drugs (Cetinkal et al, 2010;Dalgic et al, 2009;Guvenc et al, 2013;Simsek et al, 2012;Temiz et al, 2009;Whitsel et al, 2002). In this study, it was observed that the width of the neural tube was altered with the Riparin III concentrations evaluated.…”
Section: Discussionmentioning
confidence: 70%
“…For example, vascularization decreases in the 72 h chicken embryo in responses to diesel exhaust particles (DEP), and between 30-80% of exposed embryos were poorly developed (Simsek et al, 2012).…”
Section: Organic Toxicants As Developmental Disruptorsmentioning
confidence: 99%
“…Each group contained 12 embryos. After 30 hours of incubation, the eggs were in stage 9 according to Hamburger-Hamilton series (7,12). Egg shells were opened (under 4x magnifications) and then embryonic discs were identified.…”
Section: Incubation and Injection Of Chicken Embryosmentioning
confidence: 99%